(untitled) (Scientific journal of the Fergana State University, 2024)
The study of the landscapes of the Shahimardonsoy River Basin, which gave rise to the “Shvetsaria of Uzbekistan” in the south-east of Uzbekistan, is one of the pressing problems of the present day. The main purpose of our research is to improve the reclamation and geoecological condition of the shahimardonsoy River Basin landscapes, to make the necessary scientific and practical suggestions and recommendations for the quality of river water and its protection. Within the framework of the scientific work, we covered the research work using the basin research method of river basin lnadshafts in the study of the landscape area, and multi-stage neutron-activation tahili in the study of the chemical composition of water, aerospace methods of landscape. During the study, it was found that the waters of the Shoshimardonsoy River Basin are harsh compared to those at the beginning of the river and have a relatively high content of antimony and Mercury. The reason for this is the pollution of the atmosphere of industrial enterprises in the area, as well as the heavy use of river water for economic purposes. Necessary measures have been developed to ensure that the health of the population and its impact on agricultural crops, the ecology of the territory is not affected.